La Nanoelectrónica y la Electrónica Molecular - Seminario y Cols., Jorge M. (2018)
Nanotechnology offers tools for the design of automated sensors capable of neutralizing toxic agents through the development of logical operations and communication of information. The use of molecular components in the manufacture of nanosensors is advantageous because of the high capacity of information transmission, efficiency and speed of operations. The goal is to develop intelligent nanosensors using logical operators based on the molecular electrostatic potential interactions and the transport of information through vibrational signals. The current work shows preliminary results based on basic principles of matter, such as quantum mechanics, molecular mechanics and molecular dynamics.The cascades of molecular gates would operate through signals based on molecular electrostatic potential. These logical gate arrays will allow us to perform all kind of mathematical functions. The positive and negative values of the molecular electrostatic potential will be the input and output signals of a logic gate. Finally, the information contained in the output will be transported through linear molecules by fluctuations of vibrational modes in the terahertz (THz) range.